2021
DOI: 10.3390/ijerph18189678
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Academic Emotions on Learning Effects: A Systematic Review

Abstract: Academic emotions can have different influences on learning effects, but these have not been systematically studied. In this paper, we objectively evaluate the influence of various academic emotions on learning effects and studied the relationship between positive and negative academic emotions and learning effects by using five electronic databases, including WOS, EMBASE, PubMed, PsycINFO, and Google Scholar. According to established standards, a total of 14 articles from 506 articles were included in the ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
13
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 79 publications
(230 reference statements)
4
13
0
2
Order By: Relevance
“…In relation to academic performance in our scan, the student with the most positive and neutral and least negative emotion scored excellent. This is in line with the literature, which agrees that positive emotions are related to better learning processes [23], while negative emotions have a negative effect [24], or may have ambivalent effects [12]. A future study would be necessary to establish correlations between emotions and academic performance, controlling for variables such as absenteeism.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…In relation to academic performance in our scan, the student with the most positive and neutral and least negative emotion scored excellent. This is in line with the literature, which agrees that positive emotions are related to better learning processes [23], while negative emotions have a negative effect [24], or may have ambivalent effects [12]. A future study would be necessary to establish correlations between emotions and academic performance, controlling for variables such as absenteeism.…”
Section: Discussionsupporting
confidence: 85%
“…Understanding students' emotions, especially during the classroom time, can help to improve the positive classroom emotional climate towards promoting academic achievement [11]. A recent systematic review [12] about academic emotions, students' emotions experienced in achievement and academic contexts [13], and the effects on learning, showed that, compared with negative academic emotions, positive academic emotions may be more effective at improving certain aspects of learning ef-fects, especially in high school and college students.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, Wang et al (2022) found no significant correlation between learning engagement and negative achievement emotions. These results broadly are in agreement with previous reviews (e.g., Tan et al, 2021).…”
Section: Culties In Determining the E Ects Of Negative Achievement Em...supporting
confidence: 94%
“…Similarly, another literature review concluded that a positive correlation was found between enjoyment and performance, and negative correlations were found for both anger and boredom (Camacho-Morles et al, 2021). Meanwhile, Tan et al (2021) reported that positive emotions were better than negative ones at enhancing learning effects.…”
Section: Previous Reviews Of Achievement Emotionsmentioning
confidence: 95%
“…The current turn in the research of learning in higher education involves emotions and the exploration of psychosocial variables. Approaches to learning and learning styles have been related to academic emotions (Postareff et al, 2017;Tan et al, 2021). Moreover, in our recent research, learning has been linked to variables traditionally associated with mental health (Karagiannopoulou et al, 2020).…”
Section: Introductionmentioning
confidence: 99%